2009
DOI: 10.1128/iai.00679-08
|View full text |Cite
|
Sign up to set email alerts
|

Shiga Toxin 2 Targets the Murine Renal Collecting Duct Epithelium

Abstract: Hemolytic-uremic syndrome (HUS) caused by Shiga toxin-producingEscherichia coli infection is a leading cause of pediatric acute renal failure. Bacterial toxins produced in the gut enter the circulation and cause a systemic toxemia and targeted cell damage. It had been previously shown that injection of Shiga toxin 2 (Stx2) and lipopolysaccharide (LPS) caused signs and symptoms of HUS in mice, but the mechanism leading to renal failure remained uncharacterized. The current study elucidated that murine cells of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
93
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 79 publications
(130 reference statements)
11
93
0
Order By: Relevance
“…The role of apoptosis in Stx-mediated disease is also unclear. Several studies utilizing mouse models have observed apoptosis in renal cells following treatment with Stx (23,42,47), while other studies have observed necrosis (10,29,37,46,58,60).…”
Section: Discussionmentioning
confidence: 99%
“…The role of apoptosis in Stx-mediated disease is also unclear. Several studies utilizing mouse models have observed apoptosis in renal cells following treatment with Stx (23,42,47), while other studies have observed necrosis (10,29,37,46,58,60).…”
Section: Discussionmentioning
confidence: 99%
“…Mice injected with this dose of Stx2 usually develop symptoms after 3-4 days. 4,28 Mice were euthanized before symptoms developed in order to detect early apoptotic changes.…”
Section: Ouabain Protects Kidneys From Apoptosis In Stx2-treated Micementioning
confidence: 99%
“…3 Apoptosis is a major manifestation of Stx2 toxicity, as shown in biopsy samples from patients with HUS and in kidneys from mice inoculated with Stx2-producing versus Stx-nonproducing E. coli O157:H7, those treated with Stx2, and Stx2-exposed cells. 1,4,5 The mechanism by which Stx2 activates apoptotic pathways is not fully understood, but several lines of evidence suggest that it involves activation of caspase-8 and the intrinsic, mitochondrial pathway. It is well documented that Stx2 increases caspase-8 expression.…”
mentioning
confidence: 99%
“…Injection of Stx into mice results in the induction of proinflammatory cytokines, vascular damage, hemolysis, and renal damage (47)(48)(49)(50), but in contrast to piglet and rabbit infection models (23, 51-53), STEC strain originally isolated from ground beef (66). In preliminary screening of these C. rodentium lysogens, only C. rodentium (Ί1720a-02) produced significant amounts of toxin in vitro or caused systemic disease in mice (data not shown; see Figure 1).…”
Section: Introductionmentioning
confidence: 99%